IMPLEMENTASI PERATURAN BUPATI PONOROGO NOMOR 23 TAHUN 2019 TENTANG MASTERPLAN DAN ROADMAP TEKNOLOGI INFORMASI DAN KOMUNIKASI KABUPATEN PONOROGO TAHUN 2019 - 2023 - Joni Sulistyono (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The Master Plan and Information and Communication Technology Roadmappolicies in Ponorogo Regency have been implemented. However, there are stilldeficiencies in its implementation. These deficiencies include the results ofcommunication that have not been implemented properly, resources consisting ofstrategic plans, main duties and authority of cooperation do not provide supportfor policy implementation, the disposition of outstanding policy implementers hasnot been followed by a good reward system and the existing organizationalstructure has not implemented the program. and activities that are relevant to thetargets set.Keywords: Communication, Resources, Disposition, Bureaucratic Structure